Net solar generation potential from urban rooftops in Los Angeles. (July 2020) - Porse, Erik; Fournier, Eric; Cheng, Dan; Hirashiki, Claire; Gustafson, Hannah; Federico, Felicia; Pincetl, Stephanie
Abstract: Rooftops provide accessible locations for solar energy installations. While rooftop solar arrays can offset in-building electricity needs, they may also stress electric grid operations. Here we present an analysis of net electricity generation potential from distributed rooftop solar in Los Angeles. We integrate spatial and temporal data for property-level electricity demands, rooftop solar generation potential, and grid capacity constraints to estimate the potential for solar to meet on-site demands and supply net exports to the electric grid. In the study area with 1.2 million parcels, rooftop solar could meet 7200 Gigawatt Hours (GWh) of on-site building demands (~29% of demand). Overall potential net generation is negative, meaning buildings use more electricity than they can produce. Yet, cumulative net export potential from solar to grid circuits is 16, 400 GWh. Current policies that regulate solar array interconnection to the grid result in unutilized solar power output of 1700 MW. Lower-income and at-risk communities in LA have greater potential for exporting net solar generation to the grid. This potential should be recognized through investments and policy innovations. The method demonstrates the need for considering time-dependent calculations of net solar potential and offers a template for distributed renewable energy planning in cities. Highlights: A method is presented to estimate net electricity generation from rooftop solar arrays in cities. The method considers on-site demands, grid capacity, and rooftop solar generation. In Los Angeles, rooftop solar can provide 30% of building demands and additional net grid exports. Existing policies that regulate electric grid operations limit potential rooftop solar output. Lower-income and at-risk communities have greatest capacity for solar energy exports to the grid.